2001
DOI: 10.1523/jneurosci.21-15-05546.2001
|View full text |Cite
|
Sign up to set email alerts
|

Dopamine D1 Receptor-Dependent Trafficking of Striatal NMDA Glutamate Receptors to the Postsynaptic Membrane

Abstract: Recent work has shown substantial alterations in NMDA receptor subunit expression, assembly, and phosphorylation in the dopamine-depleted striatum of a rodent 6-hydroxydopamine model of Parkinson's disease. These modifications are hypothesized to result from the trafficking of NMDA receptors between subcellular compartments. Here we show that in rat striatal tissues the NR2A and NR2B subunits in the synaptosomal membrane, and not those in the light membrane and synaptic vesicle-enriched compartments, are tyros… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

18
269
1
1

Year Published

2003
2003
2017
2017

Publication Types

Select...
8
2

Relationship

1
9

Authors

Journals

citations
Cited by 351 publications
(289 citation statements)
references
References 61 publications
18
269
1
1
Order By: Relevance
“…Previously, our studies showed that stimulation of striatal slices with a D1 agonist or NMDA led to dephosphorylation of WAVE1 at Ser310, Ser397, and Ser441, indicating neuronal activity-mediated stimulation of WAVE1 (4, 7). We anticipated that WAVE1 would be dephosphorylated in response to cocaine administration in vivo, because cocaine increases synaptic levels of dopamine, and activation of D1 is known to increase NMDA-receptor-mediated signaling (13,28,29). However, there was no significant change in phosphorylation, or of the total protein level, of WAVE1 in the striatum in response to acute injection of cocaine (45 min after 15 mg/kg) or chronic injection of cocaine (15 mg/kg daily for 14 d; 45 min after the last injection).…”
Section: Resultsmentioning
confidence: 99%
“…Previously, our studies showed that stimulation of striatal slices with a D1 agonist or NMDA led to dephosphorylation of WAVE1 at Ser310, Ser397, and Ser441, indicating neuronal activity-mediated stimulation of WAVE1 (4, 7). We anticipated that WAVE1 would be dephosphorylated in response to cocaine administration in vivo, because cocaine increases synaptic levels of dopamine, and activation of D1 is known to increase NMDA-receptor-mediated signaling (13,28,29). However, there was no significant change in phosphorylation, or of the total protein level, of WAVE1 in the striatum in response to acute injection of cocaine (45 min after 15 mg/kg) or chronic injection of cocaine (15 mg/kg daily for 14 d; 45 min after the last injection).…”
Section: Resultsmentioning
confidence: 99%
“…4B). Synaptophysin is enriched in the LP2 fraction, representing a synaptic vesicle-enriched fraction (31). In addition to LP2, synapsin I was also detected in the LP1 fraction, a fraction enriched with synaptosomal membranes (32).…”
Section: Resultsmentioning
confidence: 99%
“…It remains to be determined whether an abnormal upregulation of these postsynaptic second messenger cascade events could result in exaggerated pyramidal cell excitability in response to D 1 and NMDA, as observed in the PFC of NVHL animals. A D 1 receptor activation also induces NMDA receptor trafficking to the postsynaptic membrane (Dunah and Standaert 2001), increasing surface expression of NMDA receptors. This interaction could selectively enhance pyramidal neurons' response to NMDA and not to AMPA in the adult PFC.…”
Section: Discussionmentioning
confidence: 99%